Using requirement-functional-logical-physical models to support early assembly process planning for complex aircraft systems integration. (January 2020) - Li, Tao; Lockett, Helen; Lawson, Craig
Highlights: Aircraft assembly planning is a complex systems integration problem that requires highly expert planners. A novel method is proposed to generate an initial feasible installation and test sequence for aircraft systems. It provides a structured approach for early stage assembly process planning, combining physical and functional integration. Requirement, functional, logical and physical (RFLP) models are used to link physical assembly to product function. The main outcome is improved aircraft system assembly process planning, to support better manufacturing decision making. Abstract: The assembly line process planning connects product design and manufacturing through translating design information to assembly integration sequence. The assembly integration sequence defines the aircraft system components installation and test precedence of an assembly process. This activity is part of the complex systems integration and verification process from a systems engineering view. In this paper, the complexity of modern aircraft is defined by classifying aircraft system interactions in terms of energy flow, information data, control signals and physical connections. At the early conceptual design phase of assembly line planning, the priority task is to understand these product complexities, and generate the installation and test sequence that satisfies the designed system function and meet design requirements. This research proposes a novel method for initial assembly process planning that accounts for both physical and functional integrations. The method defines aircraft system interactions by using systems engineering concepts based on traceable RFLP (Requirement, Functional, Logical and Physical) models and generate the assembly integration sequence through a structured approach. The proposed method is implemented in an industrial software environment, and tested in a case study. The result shows the feasibility and potential benefits of the proposed method.